Pengaruh pendekatan pembelajaran kontekstual terhadap kemampuan koneksi matematika di kelas VIII SMPS Yayasan Perguruan Kristen Hosana Medan T.P. 2017/2018 - Gaol, Yulinar Lumban; Nainggolan, Jelita (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The purpose of this research is to study whether there is a significant effect by using a contextual learning approach on the mathematical connection ability of the Private Junior High School of Hosana Medan students on the Academic Year of 2017/2018. This research used an experimental method, with all the students of class VIII as the population. With the Simple Random Sampling technique, the research sample was class VIII-B. The instruments were post-test of the learning outcomes and the student’s process skills observation. From the calculation results for the post test regression linearity obtained that Fcount = 0.325, then Ha was accepted so that there is a linear relation between the contextual learning approach to the student’s mathematical connection ability. Then for the regression significant test between X and Y, it is obtained Fcount = 424,779, then Ha is accepted so that there is regression between the contextual learning approach to the student’s mathematical connection ability. Based on the results, it can be concluded that there is an influence between the contextual learning approach on the student’s mathematical connection ability on the Two-Variable Linear Equation System in class VIII of the Private Junior High School Hosana Medan.